2011
DOI: 10.4028/www.scientific.net/amr.183-185.1864
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of LLDPE/EVA/Nano-ZnO Composites

Abstract: The process parameters of LLDPE/EVA/nano-ZnO composites were optimized by two methods. Samples were prepared under the better process parameters. The dispersion morphology and the mechanical properties of material were studied by Field Emission Scanning Electron Microscope (FESEM). And the mechanical properties of LLDPE/EVA/nano-ZnO composites were tested. It was showed that the optimization method based on neural network of BP and particle swarm optimization was better than that optimization method based on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…By absorbing the impact and radiation energy levels, the polymer had no obvious stress concentration phenomenon and achieved the mechanical equilibrium state of the composite material (Li & Li, 2010). Liu & Jia (2011) reported that the tensile strength was the highest when nano-ZnO amount was 3% under the two-step, the tensile strength was increased up to about 22%, and the fracture elongation rate was increased up to about 11%. Chen et al (Chen et al, 2021) reported that with the addition of 1.0 wt% Cu-MOF, the tensile strength and elongation at break are increased to 45.7 MPa and 2.4%, respectively.…”
Section: Mechanical and Barrier Properties Of Nano-zno/hdpe Composite Filmmentioning
confidence: 99%
“…By absorbing the impact and radiation energy levels, the polymer had no obvious stress concentration phenomenon and achieved the mechanical equilibrium state of the composite material (Li & Li, 2010). Liu & Jia (2011) reported that the tensile strength was the highest when nano-ZnO amount was 3% under the two-step, the tensile strength was increased up to about 22%, and the fracture elongation rate was increased up to about 11%. Chen et al (Chen et al, 2021) reported that with the addition of 1.0 wt% Cu-MOF, the tensile strength and elongation at break are increased to 45.7 MPa and 2.4%, respectively.…”
Section: Mechanical and Barrier Properties Of Nano-zno/hdpe Composite Filmmentioning
confidence: 99%
“…Inorganic nanoparticles (e.g., nanometer ZnO, SiO 2 ) are usually incorporated into LLDPE matrix to enhance its mechanical properties 8–10 . Liu et al added 3 wt% nanometer zinc oxide particles into LLDPE matrix, and the tensile strength increased by 20% from 22.5 to 27.1 MPa 11 . However, inorganic nanoparticles are easy to arrange and stack into aggregates resulting in defects in the material 12 .…”
Section: Introductionmentioning
confidence: 99%